PTSD Coach Online–Arabic: A Randomized Controlled Pilot Trial to Examine Feasibility, Acceptability, and Preliminary Effectiveness. Issue 1 (6th November 2020) - Miller‐Graff, Laura; Ellis, Kate; Hosny, Nadine
Abstract: The Egyptian Revolution of 2011 resulted in high‐level exposure to sociopolitical violence, placing a large burden on the mental health care system that cannot be effectively met given the small number of available providers in Egypt. We conducted a nonblinded, randomized controlled pilot trial of an online, self‐directed tool for managing posttraumatic stress symptoms (PTSS). The study aimed to evaluate the feasibility, acceptability, and preliminary effectiveness of the PTSD Coach Online–Arabic. Trauma‐exposed Egyptian adults with clinically significant PTSS ( N = 87; intervention group: n = 41) completed assessments at baseline, weekly over the treatment period, posttest, and 3‐month follow‐up. Of participants who completed weekly surveys, 88.9% used the program; 22.0% of participants reported regular, weekly use. Most tools received good likeability and perceived benefit scores, but lower perceived benefit scores on three tools suggest that some content may require additional adaptation. Intent‐to‐treat analyses using multilevel modeling with multiple imputation to account for missing data were conducted. Effect sizes for PTSS were below the cutoff for small effects at posttest, d = −0.14, but demonstrated a small positive effect at 3‐months, d = −0.25. There was a small positive effect of treatment on anxiety at posttest, d = −0.37, and a medium effect at 3‐month follow‐up, d = −0.49. Treatment effects for depressed mood were below the cutoff for small effects at posttest and 3‐months, d s = −0.14 and −0.18. These findings suggest that the PTSD Coach Online–Arabic may be a promising supplemental resource for support in this setting. 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯: JOTS‐20‐0116.R3_Miller‐Graff_cantonese Traditional Chinese PTSD在線教師‐阿拉伯文:一個隨機控制的初步試驗 檢查可行性、可接受性及初步有效性 摘要 : 2011年的埃及革命導致了社會政治的高度暴力, 給精神衛生保健系統帶來了巨大負擔, 鑑於埃及現有的提供者數量很少, 這一系統無法得到有效的滿足。我們對管理創傷後壓力症狀(PTSS )的在線自我指導工具進行了非盲目的隨機對照試驗。該研究旨在評估PTSD在線阿拉伯文教師的可行性、可接受性以及初步有效性。接觸過創傷並出現臨床意義的PTSS的埃及成年人(N= 87 ;幹預組:N= 41 )在基線、治療期間每週、測試後和3個月的隨訪中完成評估。在完成每週調查的參與者中, 88.9%的人使用了該工具;22.0%的參與者報告說每周定期使用。大多數工具都獲得了良好的好感度和感知利益得分, 但三個工具的感知利益得分較低表明, 有些內容可能需要額外的調整。使用多層次模型進行了意向性治療分析, 並進行了多重歸因以考慮缺失數據。 PTSS的效應大小在測試後低於小效應的臨界點, d = ‐0.14, 但在3個月時表現出小的積極效應, d = ‐0.25 。在測試後, 治療對焦慮有一個小的積極效應, d = ‐0.37, 在3個月的隨訪中, 有一個中等效應, d = ‐0.49 。抑鬱情緒的治療效果在測試後和3個月時都低於小效果的臨界點, d = ‐0.14和‐0.18 。這些發現表明, PTSD在線教師‐阿拉伯文可能是在這種情況下提供支援的一種有希望的資源。 Simplified Chinese PTSD在线教师‐阿拉伯文:一个随机控制的初步试验 检查可行性、可接受性及初步有效性 摘要 : 2011年的埃及革命导致了社会政治的高度暴力, 给精神卫生保健系统带来了巨大负担, 鉴于埃及现有的提供者数量很少, 这一系统无法得到有效的满足。我们对管理创伤后压力症状(PTSS )的在线自我指导工具进行了非盲目的随机对照试验。该研究旨在评估PTSD在线阿拉伯文教师的可行性、可接受性以及初步有效性。接触过创伤并出现临床意义的PTSS的埃及成年人(N= 87 ;干预组:N= 41 )在基线、治疗期间每周、测试后和3个月的随访中完成评估。在完成每周调查的参与者中, 88.9%的人使用了该工具;22.0%的参与者报告说每周定期使用。大多数工具都获得了良好的好感度和感知利益得分, 但三个工具的感知利益得分较低表明, 有些内容可能需要额外的调整。使用多层次模型进行了意向性治疗分析, 并进行了多重归因以考虑缺失数据。 PTSS的效应大小在测试后低于小效应的临界点, d = ‐0.14, 但在3个月时表现出小的积极效应, d = ‐0.25 。在测试后, 治疗对焦虑有一个小的积极效应, d = ‐0.37, 在3个月的随访中, 有一个中等效应, d = ‐0.49 。抑郁情绪的治疗效果在测试后和3个月时都低于小效果的临界点, d = ‐0.14和‐0.18 。这些发现表明, PTSD在线教师‐阿拉伯文可能是在这种情况下提供支持的一种有希望的资源。